ISLAM, NILAI SOSIAL, SIKAP KEBERAGAMAAN DI TENGAH PROBLEM KEBANGSAAN - MUHAMMAD NUH, MUHAMMAD NUH (Politika: Jurnal Ilmu Politik, 2014)
Prosperous society is the goal of all religions and purpose of a nation. The spirit of nationality becomes important because of the plurality of the nation of ethnic factors, culture, region, religion, race and class. The spirit of nationality is intended as a spirit, soul and creation activities unity of Indonesia. Keywords : Pluralism, ethnicity, religion, race and class